2022
DOI: 10.1177/13694332221104276
|View full text |Cite
|
Sign up to set email alerts
|

Seismic design and numerical assessment of shape memory alloy-restrained rocking precast concrete bridge columns

Abstract: This paper introduces a class of shape memory alloy (SMA)-restrained rocking (SRR) bridge columns and numerically evaluates their response under lateral loading. SRR columns are low-damage precast concrete columns that are connected to their adjacent substructure components through two series of unbonded links, namely, SMA links and energy dissipation (ED) links. The SMA links, which are prestressed and made of superelastic Nitinol, provide the rocking joints with self-centering and dissipate a moderate amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…The other group use high strength steel bars (Cai et al, 2018; Ou et al, 2010b; Tong, et al, 2021; Wang et al, 2008; Wang et al, 2017; Zhang, et al, 2021). Others have proposed internal CFRP bars (Cai et al, 2019; Wang et al, 2012) or SMA bars (Akbarnezhad et al, 2022; Li et al, 2017; Nikbakht et al, 2015; Roh and Reinhorn, 2010, Roh et al, 2012, Tazarv and Saiidi, 2015). A new construction method of precast segmental bridge column was proposed by Sung et al (2017) using modular construction methodology as shown in Figure 3(c).…”
Section: Constructionmentioning
confidence: 99%
“…The other group use high strength steel bars (Cai et al, 2018; Ou et al, 2010b; Tong, et al, 2021; Wang et al, 2008; Wang et al, 2017; Zhang, et al, 2021). Others have proposed internal CFRP bars (Cai et al, 2019; Wang et al, 2012) or SMA bars (Akbarnezhad et al, 2022; Li et al, 2017; Nikbakht et al, 2015; Roh and Reinhorn, 2010, Roh et al, 2012, Tazarv and Saiidi, 2015). A new construction method of precast segmental bridge column was proposed by Sung et al (2017) using modular construction methodology as shown in Figure 3(c).…”
Section: Constructionmentioning
confidence: 99%